Perbaikan Sifat Perekatan Kayu Sengon dengan Perlakuan Permukaan - Sushardi; Didik Surya Hadi (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2023)
The usage in the types of wood as the raw material of industry should be appropriate with the basic nature of wood in order to produce the forest’s product with good quality. This research was aimed to : 1) learn the relationship between the different parts of wood and the treatment of surface toward glue’s nature of sengon wood and find out the factors that were most influenced, 2) Handle the weak of glue’s strength because of the influence in a part of gubal and teras wood with the treatment of the surface. The design of this research used the factorial experiment arranged in the design of completely random, with the continuing Turkey test. The factor used in this research consisted of part of the wood (gubal and teras wood) and the treatment of the surface (without treatment, NaOH, ethanol, and alcohol bensen). The observed parameter included the density, the glue’s strength, and the damage to wood because of dry and wet air. The result of this research indicated glue’s nature was really most influenced by the part of the wood and the treatment of the surface. The average rate in the best nature of glue for sengon wood was produced in the part of teras wood, namely the glue’s strength in the dry air, the wood damage in dry air, the strength of wet glue, the damage of wet wood were 42,50 kg/cm2, 80,25 %, 23,61 kg/cm2, 44,92. The average rate in the best nature of glue for sengon wood was produced in the treatment of alcohol bensen, namely the glue’s strength in dry air, the wood damage on dry air, the strength of wet glue, and the damage of wet glue were 43,47 kg/cm2, 87,513 %, 24,375 kg/cm2, and 48,62 %.